CHANGE IN THE ACTIVITY OF THROMBOPOIETIN, AS A REGULATOR OF THROMBOCYTOPOIESIS, WITH EXPERIMENTAL VIOLATION OF THE HEMOSTASIS SYSTEM - Alexander Aleksandrovich Vlasov; Tatyana Petrovna Bondar; Natalia Aleksandrovna Berezina; Vera Vladimirovna Vlasova (Современная наука и инновации)
Presented own research to study the mechanism of activity regulation of thrombocytopoiesis in experimental animals white Wistar rats in the experimental groups physiological pregnancy and in models of thrombocytopenia and thrombocytosis.